Expression Profile of Osteoclasts Following the Stimulation With Interleukin-23 in Mice - Miao CHEN,; Dan-Dan PANG,; Sheng-Ming DAI, (Archives of Rheumatology, 2020)
Objectives: This study aims to analyze the expression profile of osteoclasts (OCs) following the stimulation with interleukin 23 (IL-23) in mice, which would imply the underlying effects of IL-23 on the function of OCs in inflammatory arthritis. Materials and methods: Mature OCs were induced from bone marrow mononuclear cells of 5 male mice (age 6 weeks; weighing 18-20 g) in the presence of macrophage-colony stimulating factor (50 ng/mL) and receptor activator of nuclear factor kappa B ligand (30 ng/mL) in vitro. The Agilent SurePrint G3 Mouse GE V2.0 Microarray was used to analyze the gene expression profile of OCs stimulated with IL-23 (30 ng/mL) or vehicle. The four major IL-23-modulated genes were validated by quantitative real-time polymerase chain reaction (qPCR) analysis. Results: The expression levels of 23 genes were up-regulated and 32 genes were down-regulated by IL-23 stimulation (fold change ≥1.5 and p value <0.05). Among them, there were 37 genes with assigned gene symbols. Gene ontology analysis showed that the IL-23-regulated messenger ribonucleic acids (mRNAs) were related to positive regulation of leukocyte chemotaxis, chemokine-mediated signaling pathway and C-X-C chemokine receptors binding. The pathway analysis showed that the IL-23-regulated mRNAs were related to chemokine signaling pathway and cytokine-cytokine receptor interaction. The significant up-regulation of chemokine (C-X-C motif) ligand 1 and chemokine (C-X-C motif) ligand 2 induced by IL-23 was confirmed by qPCR. In addition, there were 18 long non-coding RNAs that were regulated by IL-23, while their function needs to be confirmed in the future. Conclusion: Expression levels of genes related to chemotaxis in OCs were up-regulated by IL-23 in mice, which imply that IL-23 may facilitate chemotaxis of OCs in inflammatory arthritis.